2009
DOI: 10.1002/jmr.980
|View full text |Cite
|
Sign up to set email alerts
|

Alchemical free energy simulations for biological complexes: powerful but temperamental …

Abstract: Free energy simulations compare multiple ligand:receptor complexes by "alchemically" transforming one into another, yielding binding free energy differences. Since their introduction in the 1980s, many technical and theoretical obstacles were surmounted, and the method ("MDFE," since molecular dynamics are often used) has matured into a powerful tool. We describe its current status, its effectiveness, and the challenges it faces. MDFE has provided chemical accuracy for many systems but remains expensive, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 152 publications
(185 reference statements)
2
58
0
Order By: Relevance
“…The MDFE method follows the horizontal legs of the cycle. Protonated histidine is reversibly transformed into its deprotonated form during a series of MD simulations and the corresponding work is derived from a thermodynamic integration formula (Simonson 2001;Aleksandrov et al 2010). For the lower leg of the thermodynamic cycle, we simulated methyl-imidazole in solution, which served as the reference molecule, whereas for the upper leg we simulated a portion of the ribosome complex.…”
Section: Alchemical MD Free-energy Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MDFE method follows the horizontal legs of the cycle. Protonated histidine is reversibly transformed into its deprotonated form during a series of MD simulations and the corresponding work is derived from a thermodynamic integration formula (Simonson 2001;Aleksandrov et al 2010). For the lower leg of the thermodynamic cycle, we simulated methyl-imidazole in solution, which served as the reference molecule, whereas for the upper leg we simulated a portion of the ribosome complex.…”
Section: Alchemical MD Free-energy Simulationsmentioning
confidence: 99%
“…The uncertainty was calculated as the standard deviation of the individual runs obtained in each direction (Aleksandrov et al 2010). This extended simulation length was necessary to correctly sample the important degrees of freedom and to obtain a low statistical uncertainty.…”
Section: Alchemical MD Free-energy Simulationsmentioning
confidence: 99%
“…The lack of a consistent optimum dielectric constant for MM-PBSA calculations has been noted www.intechopen.com by other workers (see for e.g. (Aleksandrov et al 2010)), although generally a value ε in =4 often gives satisfactory results (Aleksandrov et al, 2010;Archontis et al, 2001;Thompson et al, 2006). As a final note, MM-GB(PB)SA calculations require some degree of user expertise and planning, from the initial set-up and analysis of the MD simulations through to the binding free energy calculations themselves.…”
Section: Limitations and Caveats Of Mm-gb(pb)sa Calculationsmentioning
confidence: 81%
“…In a recent MM-PBSA study, researchers suggested that the use of ε in = 4 for a highly charged protein-ligand binding interface, ε in = 2 for a moderately charged binding interface and ε in = 1 for a hydrophobic binding interface may improve ligand ranking [16] . The lack of a consistent optimum dielectric constant for MM-PBSA calculations has been noted by other [20] , although generally a value ε in = 4 often gives satisfactory results [20][21][22] . Finally, MM-PBSA calculations require some degree of user expertise and planning, from the initial set-up and analysis of the MD simulations through to the binding free energy calculations.…”
Section: Limitations Of Mmpbsamentioning
confidence: 92%